Pengaruh Relaksasi Nafas Dalam dan Pijat Wajah Terhadap Tekanan Darah dan Stres Pada Ibu Hamil - Fenti Hasnani (Jurnal Health Sains, 2021)
Hypertension is very significant contributing to maternal and fetal morbidity and mortality so it is necessary to do preliminary screening and follow-up during pregnancy. Hypertension is a disease of the cardiovascular system that has high mortality and morbidity. High blood pressure in hypertensive patients can be overcome by pharmacological and non-pharmacological therapy. One non-pharmacological therapy is facial massage therapy and deep breathing relaxation. This research is a quantitative study with the method of Non-equivalent Control Group Design with the Control Group Post test only design approach or post test control group. The study was conducted at the Puskesmas Tanah Baru Depok. The sample amounted to 108 people who were divided into 54 people in the control group and 54 people in the intervention group. Data was collected through questionnaires and blood pressure measurement results. Based on the Mann Whitney test results obtained p-value 0.001, it can be concluded that there is a difference in the mean systolic blood pressure in pregnant women who do facial massage and deep breathing relaxation. There was a significant difference in the value of stress levels after facial massage and deep breathing relaxation at the stress level (p-value 0.001). The average stress level in pregnant women who did not take facial massage and deep breathing relaxation was 76.50 ± 25.5, while for pregnant women who did facial massage therapy and deep breathing relaxation was 60 ± 16.